Pengembangan E-LKPD Berbasis Pendekatan Contextual Teaching and Learning (CTL) pada Materi Lingkaran Dengan Konteks Anyaman - Amelia, Risky; Syutaridho; Nizar, Harisman; Rahmawati, Dyah (Media Pendidikan Matematika, 2025)
This study aims to develop E-LKPD based on the Contextual Teaching and Learning (CTL) Approach on the material of circles with a woven context for grade VIII junior high school students. This development research uses the Tessmer model consisting of a preliminary stage including analysis of students, curriculum, and teaching material needs, while the prototyping stage includes design, validation, and trial of E-LKPD. Data collection was carried out using interview methods, observations, questionnaires, and concept understanding tests. Based on the analysis results, it was found that students still experience obstacles in understanding the concept of circles due to limited context-based teaching materials and the unavailability of a curriculum that supports the integration of local wisdom, such as the use of woven rope. The developed E-LKPD is considered to have met the validity criteria (average score of 89.7%), practical (average score of 84%), and had a potential effect (average score of 88.8%). The CTL approach with a woven context increased students’ motivation, involvement, and appreciation of local culture. This study produced an E-LKPD that was suitable for use as an interactive mathematics learning media that was relevant to students’ daily lives.